Customer analytics for dummies - Sauro, Jeff (--For dummies., 2015)
Ensuring your customers are having positive experiences with your company at all levels is crucial to the success of your business. Sauro shows you how to measure each stage of the customer journey and use the right analytics to understand customer behavior and make key business decisions.